A Study on Marketing of Broilers with Reference to Retailers in Coimbatore City - Yesodha Devi, N.; Kanchana, V.S.; Sujatha, S. (Indian Journal of Marketing, 2008)
India constitutes a large potential market for poultry meat. Poultry production and consumption in India appears to be expanding rapidly, fuelled by rising incomes as well as changes in the structure of poultry production and marketing. The key structural change spurring production growth is the emergence of integrated producers, which are combining breeding, feed milling, contract growing and marketing activities, and fostering improved productive and reduced marketing cost. Presently, world poultry meat output has increased nearly eight fold, from 8.9 to 70.4 million tones over 1961-2001. India was ranked as the sixth largest poultry producer in the world, in the year 2004. Of late, India is the world’s fourth largest egg producers and fifth major producer of broilers. India has made a considerable progress in broiler production in the last three decades and the eighties was a green decade in the growth of broiler farming in India.